2000
DOI: 10.17310/ntj.2000.4s1.05
|View full text |Cite
|
Sign up to set email alerts
|

EITC Noncompliance: The Determinants of the Misreporting of Children

Abstract: Internal Revenue Service data indicate that $4.4 billion in excess EITC was claimed for tax year 1994, largely due to violations of the qualifying child eligibility criteria. I find that the probability of misreporting a child is increasing in the size of the EITC and tax benefit. The estimated effect of the EITC on noncompliance is statistically significant, but modest in size. Reducing the size and scope of the EITC could improve compliance somewhat, but it would also reduce benefits to compliant taxpayers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…An EITC recipient minimizes her overall tax liability by reporting earned income exactly equal to this kink. While the opportunity to inflate self-employment income to boost EITC payments has long existed, studies using audit data from the 1980s and early 1990s found little evidence of over-reported self-employment income among EITC recipients (Joulfaian and Rider 1996;McCubbin 2000). More recent studies, however, have shown significant bunching of reported self-employment income precisely around the first EITC kink (Saez 2010;Chetty, Friedman, and Saez 2013).…”
Section: A Bunching At the Eitc Kink Pointsmentioning
confidence: 99%
“…An EITC recipient minimizes her overall tax liability by reporting earned income exactly equal to this kink. While the opportunity to inflate self-employment income to boost EITC payments has long existed, studies using audit data from the 1980s and early 1990s found little evidence of over-reported self-employment income among EITC recipients (Joulfaian and Rider 1996;McCubbin 2000). More recent studies, however, have shown significant bunching of reported self-employment income precisely around the first EITC kink (Saez 2010;Chetty, Friedman, and Saez 2013).…”
Section: A Bunching At the Eitc Kink Pointsmentioning
confidence: 99%
“…McCubbin (2000) suggests that approximately 30 percent of noncompliance in the EITC is an intentional decision related to improperly claiming children, and there also seems to be sorne intentional noncompliance associated with filing status errors and underreporting income. There is also evidence that a significant amount of EITC noncompliance is unintentional, resulting from the complexity of the tax code, the credit, and characteristics of low-income filers, such as complicated family relationships and low levels of education and language skills (Holtzblatt and McCubbin, 2004).…”
mentioning
confidence: 99%
“…These cross-sections report 6 Recent research on dependent overclaiming focuses on the Earned Income Tax Credit (EITC). McCubbin (2000) describes data from a 1994 audit of randomly selected EITC claimants. Approximately 26% of EITC dollars claimed were overturned upon audit, and about 70% of these overclaims involved an error in claiming an EITC-qualifying child.…”
Section: Tax Return Panel Datamentioning
confidence: 99%